2000
DOI: 10.1007/s004410000260
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical classification of enteric neurons in the guinea-pig distal colon

Abstract: Previous studies have identified the chemistries, shapes, projections and electrophysiological characteristics of several populations of neurons in the distal colon of the guinea-pig but it is unknown how these characteristics correlate to define the classes of neurons present. We have used double-label immunohistochemical techniques to identify neurochemically distinct subgroups of enteric neurons in this region. On the basis of colocalisation of neurochemical markers and knowledge gained from previous studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
240
0
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(259 citation statements)
references
References 78 publications
8
240
0
11
Order By: Relevance
“…From these results, it was deduced that pacemaker cells and possibly the related smooth muscle cells contributing to the large contractions were innervated by cholinergic excitatory nerves, nitrergic inhibitory nerves, substance P-ergic excitatory nerves and NANCNN inhibitory nerves. These results agree with the type of neurons involved in gastrointestinal smooth muscle tissue (Hoyle and Burnstock, 1989;Furness et al, 1994;Kuriyama et al, 1998;Kunze and Furness 1999;Furness, 2000;Lomax and Furness, 2000), and were also in agreement with the results examined in the proximal region but not the pacemaker area of the guinea-pig colon (Kodama et al, 2010). The density of the nerves distributed in individual preparations seemed to be non-homogenous, and in general the former two were high, compared to the latter two.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…From these results, it was deduced that pacemaker cells and possibly the related smooth muscle cells contributing to the large contractions were innervated by cholinergic excitatory nerves, nitrergic inhibitory nerves, substance P-ergic excitatory nerves and NANCNN inhibitory nerves. These results agree with the type of neurons involved in gastrointestinal smooth muscle tissue (Hoyle and Burnstock, 1989;Furness et al, 1994;Kuriyama et al, 1998;Kunze and Furness 1999;Furness, 2000;Lomax and Furness, 2000), and were also in agreement with the results examined in the proximal region but not the pacemaker area of the guinea-pig colon (Kodama et al, 2010). The density of the nerves distributed in individual preparations seemed to be non-homogenous, and in general the former two were high, compared to the latter two.…”
Section: Discussionsupporting
confidence: 90%
“…Some myenteric nerves extend their axons into the mucosal layers, such as the Dogiel type II fibers (Kunze and Furness 1999;Furness, 2000;Lomax and Furness, 2000), and some of these could terminate on ICC-SMP distributed in the submucosal layer. There is a rich distribution of nerve terminals around ICC-SMP in the guinea-pig colon (Ishikawa and Komuro, 1996;Toma et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies carried out on animals have shown also the presence of VIP-ergic neurons in both the small and in the large intestine [25][26][27][28]. As mentioned previously, studies on the enteric nervous system of the large intestine with cancer were performed only in relation to changes in the number of neurons and nerve fibres containing VIP in the large intestine of the rat.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, experimental evidence has been provided to suggest that, in the regions of the guinea-pig gut [36,37], in the distal colon of the same species, -opioid receptor immunoreactivity was confined to Dogiel Type I myenteric neurons which comprise ascending excitatory motor neurons to the muscle, descending inhibitory motor neurons and descending interneurons [36,38]. In particular, the presence of -opioid receptors on ascending excitatory motor neurons, which are prevalently cholinergic, is consistent with the functional evidence that -opioid receptors mediate inhibition of acetylcholine overflow as distribution, our results indicate that all the four conventional PKC isoforms are expressed in myenteric neurons of the guinea pig colon.…”
Section: Discussionmentioning
confidence: 53%